2008
DOI: 10.1021/am800020k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Microstructure of a Hyperbranched Polymer and Nanoclay Loading on the Morphology and Properties of Novel Polyurethane Nanocomposites

Abstract: Novel polyurethane nanocomposites based on toluene diisocyanate, poly(propylene glycol), various hyperbranched polymers (HBPs), and layered silicate were synthesized with the aim of determining the effect of the layered silicate loading and the functionality of HBP on the structure and properties of polyurethane nanocomposites. The microstructure of the nanocomposites was investigated by X-ray diffraction analysis and high-resolution transmission electron microscopy. It was found that exfoliated morphology and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 57 publications
1
52
1
Order By: Relevance
“…By applying a slight pressure, a releasable bond to the substrate is formed (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). In many PSA applications, a controlled release of the adhesive bond is desired, making use of the ability to undergo several cycles of bonding and detaching.…”
Section: Introductionmentioning
confidence: 99%
“…By applying a slight pressure, a releasable bond to the substrate is formed (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). In many PSA applications, a controlled release of the adhesive bond is desired, making use of the ability to undergo several cycles of bonding and detaching.…”
Section: Introductionmentioning
confidence: 99%
“…This is mainly attributed to the improved adhesion between the polymer matrix and nanoparticles (Van der Waals interaction between PS and CdS nanoparticles, which is confirmed from the FTIR spectra). As a result of this improved adhesion, the nanoparticles can restrict the segmental motion near the organic–inorganic interface [49–52]. It is also observed that T g increases with the addition of CdS nanoparticles up to 4 wt% into the PS matrix and decreases for 6 and 8 wt% of CdS nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…Again, the high aspect ratio and large surface area of the nanoclay contributed to the adhesion between the polymer molecules and the OMMT layers. As a result, the reinforcing phase of the nanocomposite was efficient at bearing high stress 25 and contributed to the improvement in tensile strength. Motion of the polymer chains was effectively constrained because of stronger interactions between OMMT layers and the polymer molecules associated with a larger contact surface.…”
Section: Performance Characteristics Of the Nanocompositesmentioning
confidence: 99%